The psychology of bereavement and mourning rituals in a Northern Sotho community - Makgahlela, Mpsanyana Wilson (University of Limpopo, 2016)
The Euro-American bereavement literature has greatly contributed towards the management of the bereaved over centuries by psychologists. However, much of the literature lacks inclusion of non-westerners‘ bereavement and grief experiences. In light of this historical weakness, the aim of the present study was to explore bereavement and mourning in the Northern Sotho community with a view to identifying and documenting the psychological themes embedded in this culturally constructed experience. A total of fourteen participants (male = 7; females = 7; aged between 35 and 85) were selected using the snowball sampling method. The data were collected using in-depth semi-structured interviews. Hycner‘s adapted phenomenological explicitation method was used to analyse the data. The four major themes that emerged during data-explicitation were; a). The influence of belief systems on the conception of death; b). The experience and expression of the pain of grief; c). Diverse bereavement rituals and cultural practices that are performed to heal the bereaved, and; d). Various mechanisms that are put in place to quarantine the bereaved from spreading death contaminations. The study findings suggest that the conceptualisation, experience, and expression of bereavement is profoundly influenced by an interplay of a plethora of factors that include people‘s varying worldviews, cultural practices, and now, the emerging new-global culture. Based on the findings of the study, a culturally informed bereavement conceptual model was developed. The model proposes that a clinician should be guided by four domains when providing grief counselling. The first domain involves the clinician looking into the client‘s belief system and how this influences the client‘s grieving process. The second domain entails analysis of the nature and circumstances surrounding death. In the third domain, the clinician will need to examine the influence of various psychological, physical and socioeconomic factors on the client‘s grief. And lastly, the clinician will need to determine the intensity and duration of the grief experience. It is envisaged that this model could help in the provision of person-centred grief counselling services within a multicultural context. The study further elaborates on the lessons the field of psychology could learn from the study findings. The findings are also discussed in the context of the emerging field of Africa psychology.
Thesis (Ph.D. ( Psychology)) -- University of Limpopo, 2016
Keywords: Bereavement; Mourning rituals; Bereavement -- Psychological aspects; Rites and ceremonies -- South Africa -- Limpopo; Pedi (African People) -- South Africa -- Limpopo